Strategi Pengembangan Komoditi Unggulan Tanaman Pangan dan Palawija di Kecamatan Bonegunu Kabupaten Buton Utara di Masa Pandemi Covid 19 - Yusran, Yusran; Nikoyan, Anas (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
The agricultural sector is one of the main driving sectors of the North Buton Regency during the covid 19 pandemic, Bonegunu District, North Buton Regency is trying to develop superior commodities for the food crops secondary crops sub-sector. The problem in developing food crops and secondary crops during the COVID-19 pandemic is that they have not determined only commodities and strategies for growing and secondary crops during the COVID-19 pandemic. This study aims to determine the potential for developing superior commodities of food crops and secondary crops before and during the COVID-19 pandemic. 19 and to find out the strategy for developing excellent commodities of food crops and secondary crops during the covid 19 pandemic. The data analysis in this study was LQ and SWOT analysis. The results showed that before the covid 19 pandemic, rice was the leading commodity, but the commodity was not during the covid 19 pandemic. Commodities that experienced an increase or were superior during the COVID-19 pandemic were sweet potatoes and green beans. The strategy for developing food crops and secondary crops in Bonegunu District, North Buton Regency during the COVID-19 pandemic includes the SO strategy, Building partnerships between the central and regional governments of North Buton Regency and the private sector, Expansion of the development area, ST Strategy, Expansion of marketing networks through online media, Setting prices government purchases (HPP) at the farmer level, WO strategy, increasing the number of adequate facilities and infrastructure, increasing farmer human resources through training and mentoring, expanding the use of modern technology, WT strategy, increasing the use of superior seeds, fertilizers, and integrated pest control